Attentional bias modification for addictive behaviors: clinical implications. (19th March 2014) - Cox, W. Miles; Fadardi, Javad S.; Intriligator, James M.; Klinger, Eric
Abstract : When a person has a goal of drinking alcohol or using another addictive substance, the person appears to be automatically distracted by stimuli related to the goal. Because the attentional bias might propel the person to use the substance, an intervention might help modify it. In this article, we discuss techniques that have been developed to help people overcome their attentional bias for alcohol, smoking-related stimuli, drugs, or unhealthy food. We also discuss how these techniques are being adapted for use on mobile devices. The latter would allow people with an addictive behavior to use the attentional training in privacy and as frequently as needed. The attentional training techniques discussed here appear to have several advantages. They are inexpensive, can be fun to use, and have flexibility in when, where, and how often they are used. The evidence so far also suggests that they are effective.